Research of Positioning Accuracy of the Cycloid Ball Planetary Transmission - Su Hui; Yang Kun; Yu Qinghuan; Hou-Tian Bowen (Jixie chuandong)
In view of the influence of elastic deformation of ball reducer gear meshing point on the transmission performance,a method for locating the positioning accuracy by using the stiffness coefficient of the mesh point is proposed. The mechanism of the coupling positioning accuracy is analyzed. The mechanical model of the meshing pair is established,the delay angle of meshing pair is derived by using the torque balance equation. The position precision of the meshing pair is introduced by applying the backward rotation angle of meshing. The influence of structural parameters on the accuracy of positioning is analyzed. The results show that the hysteresis curve of the transmission mechanism is periodic fluctuation. The mechanism behind the angle of the main source of the reduction of the gear mesh. The amplitude variation is mainly influenced by the constant velocity engagement. The change of structure parameters has obvious influence on the accuracy of the positioning. The theoretical support for the transmission performance improvement and structural optimization of the planetary transmission of the steel ball is provided by research results.